Comparative Evaluation of Yeast Selenium and Sodium selenite Supplementation on Fertility, Hatchability and Antioxidant Status in Dual Purpose Laying Hens - Dodamani, Pramod; Venkataramaiah, Malathi; Jolapure, Abhishek Mahadev; Vedamurthy, Deepthi; Jayanaik (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Selenium (Se) is an essential trace element, involved in many biological processes in animals, such as antioxidant status, reproduction, immunity, reproduction, and thyroid hormone metabolism. Dual purpose Giriraja (180) hens of 30 weeks of age were randomly distributed into 4 treatment groups having 5 replicates of 10 (1 male + 9 females) birds each. Treatment groups were divided based on additional selenium supplementation to the basal diet. Accordingly, the basal diet was T1, with further addition of sodium selenite, sodium selenite + selenium-enriched yeast and selenium enriched yeast @ 0.5, 0.3 + 0.2, and 0.5 mg Se/kg basal diet to form diets for T2, T3, and T4, respectively. The experimental period was for 8 weeks @ 150g feed/day/bird. Fertility, hatchability and antioxidant status viz., levels of Glutathione peroxidase, Superoxide dismutase and Catalase were assessed. The addition of different sources of Se alone and their combination did not show any significant difference in fertility and hatchability parameters at the end of 4th and 8th weeks of the study. Similarly, no significant improvement was seen in the antioxidant status of the birds at the end of the experiment. In conclusion, the requirement of selenium, in layer (0.05-0.08mg/kg diet) can be met with the amount of Se present in the feed raw material. Hence additional selenium supplementation may not be required under normal environment and production conditions.